University physics : For engineering and science students - Chaddha, Gurbachan S. (New Delhi: Narosa Publishing House, 2015)
UNIVERSITY PHYSICS comprises of Five chapters (1-3 and 11-12) on waves seven chapters (4-10) on electricity and magnetism and twelve chapters (13 24) on Modern Physics (Appendix deals with a chapter on Elements of Crystallography). The book also comprises two courses for undergraduate students in Science, one on Electricity and Magnetism and the other on Modern Physics. Its exhaustiveness makes it suitable as a text book for engineering colleges.
Includes appendix, bibliography and Index
Keywords: Physics -- Electricity and magnetism -- Waves -- Modern physics